A study on the analysis of satisfaction with liberal arts education based on core competencies of H University - Ki, Kim Yong- (Nurture, 2024)
Purpose: The purpose of this study is to investigate the satisfaction of liberal arts education of H University students to identify the correlation between each other and to design a new liberal arts curriculum as an analysis result. Findings: The purpose of this study is to design the general education of H University for the future year by analyzing the satisfaction with the general education of H University. First, in the results of analyzing major items of general education, the general education programs showed high satisfaction while the administrative area showed a bit low satisfaction. Second, students’ learning activities and professors of general education showed the highest satisfaction while the qualitative level of general education courses, guidance and advice of general education support facilities showed the lowest satisfaction in the results of analyzing detailed items of general education. Third, it is the demand for new general education courses. The new general education courses were classified into areas of progressiveness, coexistence and inquiry. Conclusion: Therefore, H University has increased the satisfaction of the administrative domain, improved the quality level and developed a new curriculum based on demand. There is a need for improvement in the opening.